Deskripsi Permainan Tradisional Ponti dalam Menumbuhkan Nilai-Nilai Kebersamaan Anak Usia Dini - Siti Afrianti Asdik Labedi; Mita Sari; Nur Ain Yusuf; Fitra Mulyani Abdullah; Sri Yulita Sa'ban; Agiska Katiili (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the role of the traditional Ponti game in fostering values ​​of togetherness in early childhood at PAUD Kiddi Care Gorontalo. The Ponti game is a typical Gorontalo game that contains educational values ​​such as honesty, cooperation, discipline, sportsmanship, and tolerance. Using a descriptive qualitative approach, data were collected through direct observation, semi-structured interviews with teachers and principals, and documentation of children's activities while playing. The results of the observations showed that children showed increased social skills, the ability to work together, and the development of positive attitudes such as honesty and sportsmanship during the game. However, several challenges were also identified, including children's limited understanding of the game's rules, fear of losing, and inadequate play facilities, which hindered the optimal implementation of activities. Interviews with teachers and principals revealed that the Ponti game plays a major role in shaping children's social character and strengthening local cultural identity. However, intensive guidance, emotional habituation, and support facilities are needed to maximize the benefits of this game. These findings suggest that the traditional Ponti game is not only an effective medium of entertainment but also a fun and contextual learning tool that can shape children's character as a whole. Therefore, Ponti games need to be integrated consistently into early childhood learning activities and supported by cultural preservation programs and relevant education policies.